Gender and age effects on the incidence and severity of chemotherapy-induced neuropathic pain: a propensity score matching analysis - Andreas A. Argyriou; Roser Velasco; Foteini Kalofonou; Pantelis Litsardopoulos; Montse Alemany; Dimitrios Rikos; Haralabos P. Kalofonos; Jordi Bruna (BMC Cancer)
Abstract Objective To determine whether the clinical phenotype of chemotherapy-induced neuropathic pain (CINP) varies based on the gender and age of patients. Methods Retrospective, file-based analysis of cancer patients who received any conventional standard of care chemotherapy and were referred to assess the extent of painful chemotherapy-induced peripheral neurotoxicity (CIPN). A Propensity Score Matching Analysis (PSMA) was conducted to create balanced cohorts; accounting for variables that could impact the incidence and severity of CINP in CIPN patients. A total of 205 males and 295 females were initially included, and after PSMA, 191 patients of each gender were equally matched; totaling 382 patients. These patients were divided according to their age to those aged ≤65 years (group I, n=216) and patients aged ≥66 years (group II, n=166). CINP was assessed using the pain intensity numerical rating scale (PI-NRS) and the Douleur Neuropathique-4 questionnaire (DN4). The severity of CIPN was graded with Total Neuropathy Score-clinical (TNSc®). Results The incidence of CINP was similar between males and females (27.2% vs. 27.7%; p = 1). The same applied for the DN4 scorings at CINP onset (median 7; p = 0.9). The severity of CINP at the end of chemotherapy, according to PI-NRS, was 7 (range:6–9) for males vs. 7 (range: 5–8) for females (p = 0.09), while at 3 months post-chemotherapy the PI-NRS scorings were comparable (p = 0.56). However, males tended towards higher rates of severe CINP (PI-NRS ≥ 7) [males: 59.5%, females: 40.5%; p = 0.1], compared to female patients, despite having lower CIPN severities, according to TNSc® scoring. No statistically significant differences were observed in the incidence (25% vs. 30.7%; p = 0.214) and severity (mean PI-NRS difference p = 0.584) of CINP between age groups. Older male patients presented a higher likelihood (OR: 1.08; 95CI: 1.01–1.16; p = 0.027) of severe pain (PI-NRS ≥ 7) at the end of chemotherapy, compared to their younger counterparts. Conclusion There were no significant differences found between the occurrence and severity of CINP, based on gender or age. However, older men had more severe pain raters (PI-NRS), while scoring lower in TNSc® severities.